UPAYA MENINGKATKAN KETERAMPILAN TEKNIK DASAR PASSING SEPAK BOLA MELALUI MODIFIKASI PERMAINAN CROSSBAR COLOUR - Sani Yudha Syahidu; Erna Fitriatun (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2022)
The purpose of this Classroom Action Research is to find out to what extent the Crossbar Color game can increase the effectiveness of learning soccer passing in Grade VII MTs students. NM Addinul Qayyim Kapek, Gunungsari District, West Lombok Regency. Data collection in this Classroom Action Research consists of tests and observations. The subjects of this study were students of class VII MTs. NM Addinul Qayyim Kapek Gunungsari District with a total of 21 students. The instruments in this study were (cognitive) multiple choice tests, (psychomotor) performance tests and (affective) student character observation sheets, and this research was a classroom action research (CAR) In the initial conditions that meet the minimum completeness criteria (KKM) as many as 9 students or 42%, in the first action that meets the minimum completeness criteria (KKM) as many as 15 students or 71% and in the second action which meets the minimum completeness criteria (KKM) as many as 18 students or 85%. Based on the results of the initial conditions, actions I and II show that learning soccer passing through a modification of the crossbar color game can improve student learning outcomes.